CLONING AND EXPRESSION OF MCE1A GENE FROM MYCOBACTERIUM TUBERCULOSIS BEIJING AND H37RV STRAIN FOR VACCINE CANDIDATE DEVELOPMENT - Indriarini, Desi; Rukmana, Andriansjah; Yasmon, Andi (African Journal of Infectious Diseases (AJID), 2018)
Background: Tuberculosis remains the leading cause of death in the world, especially wherever poverty, malnutrition and poor housing prevail. Mycobacterium tuberculosis Beijing strain is the most common strain that causes tuberculosis in Indonesia. The wide spread of tuberculosis has been further aggravated by HIV-AIDS and drug resistance. Unfortunately, Bacille Calmette-Guerin (BCG) as the current vaccine has different protection function and efficacy. According to function analysis, mce1A gene was predicted to have a role in host invasion and survival of Mycobacterium tuberculosis in human macrophages. Materials and Methods: We performed cloning and protein expression of Mce1A gene of Mycobacterium tuberculosis Beijing strain as local isolate and standard strain H37Rv as a comparison on the expression system Escherichia coli BL21(DE3). Mce1A gene from the strains were amplified by PCR and inserted into the vector pET28a. Each resulting recombinant plasmid was subsequently transformed into E. coli BL21(DE3) and Mce1A protein was expressed with IPTG induction. Results: E. coli BL21(DE3) was succesfully transformed with a recombinant plasmid that contains the Mce1A gene insert with correct orientation and reading frame. There was no mutation found in the amino acids sequence for B and T cell epitope. Mce1A expression in E. coli BL21(DE3) showed a protein band that was higher than expected. The protein was confirmed with Western blotting using anti-His detector. Conclusion: We assumed that Mce1A recombinant protein that has been expressed in E. coli BL21(DE3) is in their dimeric form or alternatively formed aggregates of different sizes.